Джерела антропонімів у романі П. Куліша «Чорна рада» - Федорук, О. (Слово і Час, 2020)
У статті класифіковано джерела антропонімів у різних редакціях роману П. Куліша «Чорна рада». Визначено три типи джерел: історичні прототипи, імена і прізвища осіб із Кулішевого оточення, документальні джерела. Запроваджено в науковий ужиток нове джерело антропонімів роману — Кулішеві виписки з реєстру козацьких полків Гетьманщини (1741). Тут містяться антропоніми Василь Невольник, Пугач, Петро Сердюк, Тарануха, Чепурний, Черевань, Тур, Шрамко і Шрамченко, Шкода, які автор використав у різних редакціях твору. Частина цих антропонімів Кулішеві була відома з дитинства як прізвища мешканців м. Воронежа (Черевань, Шрамченко) та товаришів (Сердюков). The paper analyzes different sources of anthroponyms in the original and final texts of P. Kulish’s novel “Chorna Rada: Khronika 1663 Roku” (“The Black Council: A Chronicle of the Year 1663”). Three types of sources have been identified: the historical prototypes, names and surnames of Kulish’s friends, and archival (documentary) records. In addition, numerous notes in the early editions of the Russian novel contain references to the works of various people (M. Markevych, D. Bantysh-Kamenskyi, V. Kokhovskyi, etc.). The last group of anthroponyms stands outside of the plot, and the paper does not focus on it. The historical and autobiographical sources of anthroponyms are generally known. Among the first are prototypes of two hetmans — Yakym Somko and Ivan Briukhovetskyi, military secretary M. Vukhaievych, regimental osaul M. Hvyntovka. The second group comprises the occasional characters Hordii Kostomara (a historian M. Kostomarov), Ivan Yusko (a teacher I. Yuskevych-Kraskovskyi), Hulak (M. Hulak, the founder of The Brotherhood of Saints Cyril and Methodius), Bilozerets (Kulish’s brother-in-law V. Bilozerskyi), Petro Serdiuk (Kulish’s close friend Petro Serdiukov), Oleksa Senchylo (teacher Oleksa Senchylo- Stefanovskyi). In the novel, Kulish drew the love line as a projection of his relationship with Oleksandra Bilozerska and her mother Motrona. The characters of Petro Shramenko, Lesia Cherevanivna and her mother Melaniia have an autobiographical basis. Accordingly, Lesia’s name was also taken from real life. The third group of sources supplying the anthroponyms is archival records. The paper analуzes Kulish’s extracts from the roster of Cossack regiments of the Hetmanate (1741). This source wasn’t used previously. It contains the anthroponyms Vasyl Nevolnyk (‘Slave’), Puhach, Petro Serdiuk, Taranukha, Chepurnyi, Cherevan, Tur, Shramko and Shramchenko, Shkoda, which the author used in various editions of the novel.